THE TEXTBOOK AS AN OBJECT OF STUDY FOR ETHNIC-RACIAL THEMES - Tomaz, Tatiane Balbino Cordeiro; de Carvalho, Maria de Lourdes Guimarães (Seven Editora, 2026)
This article presents the results of an investigation conducted to determine whether textbooks address Afro-Brazilian literature in a way that ensures students critically question ethnic-racial issues, and whether the proposed teaching activities are adequate for addressing this theme. Its objectives were: to describe, analytically and critically, the approaches to ethnic-racial themes, especially those related to Afro-Brazilian literature, in a sample of Portuguese language textbooks intended for basic education; and to present contributions to support the deepening of this theme in the classroom at this level of education. It is a qualitative and descriptive research, based on official documents and authors who discuss textbooks and Afro-Brazilian literature. The results demonstrate a lack of a relevant approach to Afro-Brazilian literature, which constitutes a significant flaw, because by ignoring these issues, the work fails to contribute to the formation of an inclusive education capable of fostering critical reflection on racism, social inequalities, and the richness of Afro-Brazilian culture.